Validity and Reliability Testing of the Turkish Version of the “Scale of Perception of Nursing Activities That Contribute to Nursing Care Quality (EPAECQC)” - Yilmaz, Aysun Ture; Demirsoy, Nilufer; Martins, MM (Prof Despina Sapountzi-Krepia, 2018)
Background: Measuring nurses’ awareness of healthcare quality is another approach that has come to the fore in recent years. A survey of literature does not provide any research that focuses on the assessment of healthcare services from the perspective of nurses in Turkey. Aim: The aim of this study is to test the validity and reliability of the Turkish version of the “(EPAECQC)”, developed by Martins et al., in Portugal in 2006. Method: The sample of this study consisted of 211 nurses employed in the Education and Research Hospital, Faculty of Medicine, Eskisehir Osmangazi University. The English version of the “Scale of Perception of Nursing Activities That Contribute to Nursing Care Quality (EPAECQC)” was translated into Turkish and then back translated. Confirmatory factor analysis was conducted on LISREL to test validity. Internal consistency based on Cronbach’s α and item-total correlations was used to test reliability. The scale comprises 25 items and seven sub-dimensions. Item scores are based on a four-point Likert-type scale. Results: The study was conducted with 211 nurses working in Hospital of Eskisehir Osmangazi University. The nurses’ average age was 28.31 ± 6.12. In the sample, 167 nurses (79.1%) were female, and 113 nurses (53.6%) held an undergraduate degree. Item-total correlations were higher than 0.30, and alpha reliability coefficients of sub-factors varied from 0.716 to 0.894. This study also calculated fit indices of the 25-item model developed to measure nursing care quality. The results are as follows: x2/sd=334.35/209=1.59; p<0.01, root mean square error of approximation (RMSEA)=0.053; standardized root mean square (S-RMR)=0.05; comparative fit index (CFI)=0.98. Conclusion: As a result, the Turkish version of the EPAECQC is of acceptable psychometric quality. The Turkish version of the scale is a valid and reliable instrument that can be used to measure the perceptions of Nurses
Keywords: Nursing Care; Quality; Reliability